IMPROVING STUDENT LEARNING OUTCOMES MATHEMATICS THROUGH LEARNING MODELS PROBLEM BASED LEARNING - Maslianti; Azmi, Ulil (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Objective: This study aims to examine the effectiveness of the Problem-Based Learning (PBL) model in improving mathematics learning outcomes for third-grade students at SD Negeri 03 Benua Kayong by fostering critical thinking, active engagement, and problem-solving skills. Method: A qualitative descriptive approach was employed, utilizing direct observation techniques and observation sheets as instruments for data collection. The research was conducted in two cycles, with each cycle involving the implementation of PBL in thematic mathematics lessons. Results: The findings demonstrated a substantial improvement in students’ mathematics learning outcomes. Student mastery increased from 33.33% during the initial learning phase to 66.67% in Cycle 1 and reached 100% in Cycle 2. Additionally, PBL made learning more engaging and enjoyable, resulting in increased student attentiveness and participation. Novelty: This study highlights the transformative impact of PBL in elementary mathematics education, showcasing its ability to enhance learning outcomes and interest by shifting from traditional methods to an active, student-centered approach. This research contributes to the growing evidence supporting innovative teaching models for foundational mathematics skills.